2012
DOI: 10.1165/rcmb.2011-0391oc
|View full text |Cite
|
Sign up to set email alerts
|

Resistin-Like Molecule–α Regulates IL-13–Induced Chemokine Production but Not Allergen-Induced Airway Responses

Abstract: Resistin-like molecule a (Relm-a) is one of the most up-regulated gene products in allergen-and parasite-associated Th2 responses. Localized to alternatively activated macrophages, Relm-a was shown to exert an anti-inflammatory effect in parasite-induced Th2 responses, but its role in experimental asthma remains unexplored. Here, we analyzed the cellular source, the IL-4 receptors required to stimulate Relm-a production, and the role of Relm-a after experimental asthma induction by IL-4, IL-13, or multiple exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 61 publications
3
33
0
1
Order By: Relevance
“…Instead, we found that IL-13, another Th2 cytokine, was up-regulated in OVAchallenged Retnla 2/2 mice ( Figure 5). The increase in IL-13 expression with RELMa depletion is consistent with studies from other investigators (31,32). In a footpad inflammatory model induced by Nocardia cyriacigeorgica (32), IL-13 expression was elevated in the chronic inflammatory phase and inversely correlated with RELMa/ FIZZ1 expression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Instead, we found that IL-13, another Th2 cytokine, was up-regulated in OVAchallenged Retnla 2/2 mice ( Figure 5). The increase in IL-13 expression with RELMa depletion is consistent with studies from other investigators (31,32). In a footpad inflammatory model induced by Nocardia cyriacigeorgica (32), IL-13 expression was elevated in the chronic inflammatory phase and inversely correlated with RELMa/ FIZZ1 expression.…”
Section: Discussionsupporting
confidence: 90%
“…Our current data do not support a role for IL-13 in inducing pulmonary vascular remodeling, and IL-13 is not likely vital to eosinophil recruitment. However, we provide additional evidence that the Th2 response can remain robust after OVA challenge, even when RELMa is deficient, as also reported by Munitz and colleagues (31). They found no difference in inflammatory cell recruitment in Retnla 2/2 mice after IL-13 challenge compared with that in WT mice.…”
Section: Discussionsupporting
confidence: 89%
“…For example, myeloid deficiency in IL-4Ra in mice lead to a reduction in M2 markers (YM-1, Arg1, Relmα) in ovalbumin-induced allergic inflammation, but this reduction resulted in only minor changes in mucus production, eosinophilic inflammation, and collagen deposition [83]. This was mirrored by studies in which a genetic deficiency in either Relmα [84] or Arg-1 [70], had only minor effects on parameters of allergic inflammation. However, one study showed that adoptive transfer of IL-4Rα sufficient macrophages to RAG2−/− mice resulted in an enhancement of allergen-driven lung eosinophil recruitment as compared to the transfer of IL-4Rα-deficient macrophages [82].…”
Section: Mechanism(s) Of Il-13 Regulation Of the Effector Phase Ofmentioning
confidence: 99%
“…Together with epithelial cells [61], AAMs express high levels of type 2 innate response markers, such as RELMα and Ym1 (where RELM is resistin-like molecule). HES administration was found to potently suppress expression of both of these products ( Fig.…”
Section: Type 2 Innate Response Markers Are Suppressed By Hesmentioning
confidence: 99%